I’jaz Al-Quran dalam Pemikiran Yusuf Al-Qardhawi - Adik Hermawan (Madaniyah, 2016)
Yusuf Abdullah Qardawi is one of the scholars who entered the list of contemporary scholars. He is famous for his scathing criticism and his fatwas which seem controversial. Bearing the title of orphan at his age is still fairly young, making Qardhawi earnest in living life. He paid a lot of attention in the field of Islamic law, and produced many very valuable works. On the other hand, he also paid attention to the fields of the Qur'an and Sunnah. According to him al-Qur'an and as-Sunnah are the highest references of Muslims. According to Qardhawi, the phenomenon of the Koran as a miracle, is one of the studies that is quite complicated, because many debate the truth. Qardhawi argues that the diversity of forms of i'jaz al-Quran starts from I'jaz Bayani wa Adabi (i'jaz in language and literature) and I'jaz Al-Islahi Au At-Tasyri'i (miracles of the Koran in aspects Sharia teachings they contain). The third I'jaz is i'jaz al-ilmi (scientific miracle). By examining the three forms of i'jaz, it will be known that the Qur'an is truly the greatest miracle that Allah bestowed on the Prophet Muhammad, not the result of human engineering.